2021
DOI: 10.1002/slct.202101495
|View full text |Cite
|
Sign up to set email alerts
|

DFT and TD‐DFT Study on Azobenzene‐Based Dye Covalently Attached to Silane Coupling Agents: Toward Dye‐Sensitized TiO2 Catalyst and Dye‐Sensitized Solar Cell Applications

Abstract: Herein, density functional theory (DFT) and time-dependent DFT (TD-DFT) studies of 4-[(4-methoxyphenyl)diazenyl] naphthalen-1-amine (MPDNA) covalently attached to a silane coupling agent (SCA) (namely, 4-(triethoxysilyl)butane-1,2-epoxide (OTES)) with a terminal oxirane group (MPDNA-OTES) were performed to determine the influence of SCAs on the geometry of photosensitizing dyes with multiple photoisomers or conformers. CHÀ O interaction between the hydroxyl group, which was formed by an epoxy ring-opening reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…One of those research articles reports the photocatalytic activity of TiO 2 surface modified with 3-aminopropyltriethoxysilane (APTES) in degrading the methylene blue (MB) dye to an extent of 88% after 240 min of light irradiation. In another report, the role of adsorption and calcination in the photocatalytic degradation of the MB dye in the presence of APTES modified TiO 2 was investigated, in which a maximum of 96% degradation percentage after 240 min of irradiation was reported. , Takeshita has carried out computational studies at the density functional theory (DFT) and time-dependent-DFT levels on an azobenzene-based dye covalently attached to silane coupling agents (SCAs). The SCAs were coupled to a terminal oxirane group of the photosensitizing dye containing a 1-naphthylamine moiety, and it was found that the CH–O interactions can be utilized to regulate the geometry of the dye to achieve characteristics favorable for electron injection into the conduction band of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…One of those research articles reports the photocatalytic activity of TiO 2 surface modified with 3-aminopropyltriethoxysilane (APTES) in degrading the methylene blue (MB) dye to an extent of 88% after 240 min of light irradiation. In another report, the role of adsorption and calcination in the photocatalytic degradation of the MB dye in the presence of APTES modified TiO 2 was investigated, in which a maximum of 96% degradation percentage after 240 min of irradiation was reported. , Takeshita has carried out computational studies at the density functional theory (DFT) and time-dependent-DFT levels on an azobenzene-based dye covalently attached to silane coupling agents (SCAs). The SCAs were coupled to a terminal oxirane group of the photosensitizing dye containing a 1-naphthylamine moiety, and it was found that the CH–O interactions can be utilized to regulate the geometry of the dye to achieve characteristics favorable for electron injection into the conduction band of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%